2018
DOI: 10.1007/s11099-017-0733-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salt stress on low molecular antioxidants and redox state of plastoquinone and P700 in Arabidopsis thaliana (glycophyte) and Eutrema salsugineum (halophyte)

Abstract: The effects of NaCl treatment were analysed in two species of considerably different resistance. In glycophyte, the content of ascorbate decreased but lipophilic antioxidants (α-tocopherol, plastochromanol, and hydroxy-plastochromanol) increased due to 150 mM NaCl. In halophyte, 300 mM NaCl caused a significant increase in hydrophilic antioxidants (ascorbate, total glutathione) but not in the lipophilic antioxidants. The redox states of plastoquinone (PQ) and P700 were also differently modulated by salinity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…In a study on Eutrema salsugineum (Pall.) Al-Shehbaz & Warwick, 2005 grown under saline conditions, it was reported that activation of the ASC-GSH cycle is an avoidance mechanism for the single-oxygen-mediated damage in PSII, and also helps to maintain highly reduced states of the PQ pool [73].…”
Section: Discussionmentioning
confidence: 99%
“…In a study on Eutrema salsugineum (Pall.) Al-Shehbaz & Warwick, 2005 grown under saline conditions, it was reported that activation of the ASC-GSH cycle is an avoidance mechanism for the single-oxygen-mediated damage in PSII, and also helps to maintain highly reduced states of the PQ pool [73].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, low-molecular antioxidants, including AsA, GSH, α-tocopherol, β-carotene, flavonoids, and hydroquinones, have attracted interest [ 26 , 27 ]. Most researchers, however, have paid greater attention to AsA and GSH because they can be rapidly regenerated enzymatically through the AsA-GSH cycle, which plays an important role in the removal of ROS [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings led the authors to speculate that enhanced leakage of H 2 O 2 from E. salsugineum plastids preadapts the halophyte to salt stress by maintaining an up-regulated antioxidant system while preventing ROS damage. This hypothesis is further supported by the following observations: (1) the reduced activity of H 2 O 2 -detoxifying enzymes, such as ascorbate peroxidase (APX) in E. salsugineum and similar activities of catalase in E. salsugineum and Arabidopsis (Pilarska et al, 2016); and (2) the ability of E. salsugineum to sustain a highly reduced plastoquinone pool (Wiciarz et al, 2015(Wiciarz et al, , 2018. This could facilitate the persistence of the cellular H 2 O 2 signal (Bose et al, 2014).…”
Section: Halophytic Photosynthetic Performance and Protective Antioximentioning
confidence: 94%
“…Where such comparative analyses have been performed, antioxidant metabolites such as ascorbate, dehydroascorbate, and caffeic acid are either constitutively higher or accumulate to a greater extent in soil-grown E. salsugineum compared with Arabidopsis (Kazachkova et al, 2013;Eshel et al, 2017). Indeed, the avoidance of singlet oxygen production at PSII has been attributed to induction of the ascorbate-glutathione cycle in E. salsugineum (Wiciarz et al, 2018). Similarly, higher levels of thioredoxin are maintained in salt-stressed E. salsugineum, and this finding is correlated with reduced lipid peroxidation (M'rah et al, 2007).…”
Section: Halophytic Photosynthetic Performance and Protective Antioximentioning
confidence: 99%